Diseño del puente colgante Proyecto Geotérmico Las Pailas. - Calderón-Jara, Farrah (Instituto Tecnológico de Costa Rica, 2010)
This project consists in designing a suspension bridge that will support reinjection pipes for the water-bearing stratum in Las Pailas Geothermic Project. The objectives include the structural elements designs, prominent among them: cables, towers, foundations and block anchors. To achieve this, it will be used the SAP2000 Structural Analysis Software to check the design and improve it. For a 150m length and the specific loads applied to the structure, it’s required that the towers be 15m tall, the steel channels required for the pavement are W8x31 and the elements that support the pipes are 10x10x0,65 cm steel angles. The foundations consist on a 4,2x4,2m plaque with 30cm of bank, with a 2m depth, and the backing is a double #6@17,50cm metal mesh. The anchor blocks’ dimensions are 2,5x2,5x2,5m, with a double #4@15cm metal mesh in the perimeter, with an 1,65m depth cog.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Cargas aplicadas; Anclaje; Diseño estructural; Energía limpia; SAP